Dad, are they laughing at me? Fathers' vulnerable narcissism and sons' hostile attributions. (July 2022) - Bodecka-Zych, Marta; Zajenkowska, Anna; Lawrence, Claire
Abstract: Previous studies have shown that making hostile attributions, that is, attributing hostile intentions to other people mainly in ambiguous situations, increases the likelihood of aggressive behavior. Moreover, fathers' hostile attributions are associated with the aggressiveness of their children. There is also a positive relationship between hostile attributions and vulnerable narcissism among adults. However, currently, there are no empirical studies that test the connections between fathers' VN and the hostile attributions of both fathers and sons. To address this gap, the current study included 77 dyads of sons and fathers. Although fathers' hostile attributions subfactors (intentionality, blame ascription, and angry feelings in ambiguous situations) were not associated with sons' hostile attributions subfactors, fathers' angry feelings, as well as the sons' blame ascription and angry feelings, were related to fathers' vulnerable narcissism. Furthermore, fathers' vulnerable narcissism predicted sons' angry feelings which are, in turn, associated with sons' aggressiveness. The observation that fathers' vulnerable narcissism may have an impact on sons' angry feelings in ambiguous situations, which in turn is related to sons' aggression may be a crucial insight for therapeutic interventions for adolescents with aggression problems and suggests a need to focus on the father-son relationship.